(untitled) (Bangladesh Journal of Animal Science, 2013)
The objective of this research was to assess the status of cattle in respect of breeding system, quality of breeding services, their production, reproduction, health status, management system and marketing system using an in-depth baseline survey. The mean of homestead land owned by the farmers was 36.17± 32.94 decimal and most of them (48.3%) own very low homestead land (11-50 decimal). Average cultivable land owned was found as 101.52±61.044 decimal and a considerable number of farmers have medium (51-150 decimal) to high (151 onward decimal) land area. From the collected data, it is clear that most of the households have cattle and chicken. But among cattle owners, about 77.62% have lower number (1-3). Most of the farmers 69.8% use locally available grass and only 3.2 % fed exotic grass to their cows. Milk sale and consumption (52.13%) was found as main objective behind cattle rearing. Semi-intensive method of rearing was found most acceptable (77.62%) among the peri-urban farmers. Disease problem was quite high because of lack of routine vaccination where vaccination was found to be practiced by only 38.46% farmers. Indigenous cattle are of high preference among the farmers (52.45%) because of its easy management and high resistance to disease, 41.2% percent farmers preferred crossbred cattle. Main reasons behind preference for Deshi cattle were easy management (24.48%) and lower feed requirement (12.59%) whereas, reason behind crossbred preference (35.66%) was higher milk production. Artificial Insemination (AI) was preferred (61.06%) over natural service (38.94%). For artificial insemination, semen of Holstein Friesian (43.07%) was preferred where Deshi was the second most choice (32.12%). Most of the farmers (82.9%) have no idea about genotype, quality & merit of semen. Average milk yield of Deshi and crossbred genotype were found as 1.72±0.80 and 6.65±5.05 liter per day respectively whereas lactation period and dry period were found respectively as 243.98±113.13 and 92.37±63.14 days in crossbred, 249.69±106.93 and 96.58±32.06 days in Deshi cows. DOI: http://dx.doi.org/10.3329/bjas.v42i2.18485 Bang. J. Anim. Sci. 2013. 42 (2): 89-95